The Role Of Work Discipline In Improving Employee Performance Pt.Anisa Jaya Utama - Atikotul Maula; Nandang; July Yuliawati (Enrichment : Journal of Management, 2022)
The purpose of this study is to determine the role of work discipline in improving employee performance at PT. Anisa Jaya Utama. The research was conducted at PT. Anisa Jaya Utama which is located at Jl.Raya Tamelang, Krajan Hamlet, Mekarjaya Village, Purwasari District, Karawang Regency. The population in this study was 120 employees. The method used in this study is a qualitative descriptive method with data collection techniques, namely observation, interviews, and questionnaires. The result of this study is that there are still many undisciplined employees which results in decreased achievements in their performance. This can be proven from the results of observations, interviews and questionnaire results. And the solution provided so that the role of work discipline in PT. Anisa Jaya Utama is: 1) The company provides attendance tools in the form of fingerprints, or other android applications. 2) Given a letter of reprimand both oral and written. For a written reprimand the company gives SP1, SP2, SP3 until it is issued. 3) Sops are made for employee attendance, such as SOPs for incoming employees and SOPs for returning employees